The Function of English Usage on Linguistic Landscape of Padang: A Case Study on Khatib Sulaiman Street - Ikrima Zahara; Dewa Putu Wijana (English Department FBS UNP, 2022)
This study deals with linguistic landscape found on Khatiib Sulaiman Street, Padang. The aim of the study is to identify the dominant language of the monolingual, bilingual and multilingual signs and to investigate the function of English displayed on the signs. Thus, this study uses mixed method, quantitative and qualitative, since the data and the analysis of this study is in the form of pictures and text and the justification is proven by the percentage. By using multilingualism approach on a linguistic landscape research, 236 pictures of signs displayed on Khatib Sulaiman Street as the data of this study were collected on July, 2021, and then was classfied to be monolingual, bilingual, or multilingual based on the languages that exist on each sign. This research found that there are 117 signs in Bahasa Indonesia-only, 14 signs in English-only, 82 signs in Bahasa Indonesia-English, 12 signs in Bahasa Indonesia-Minangnese, 6 signs in Bahasa Indonesia-Arabic, 3 signs in Bahasa Indonesia-English-Minangnese, and 2 signs in Bahasa Indoensia-English-Arabic. Monolingual signs are dominated by Bahasa Indonesia indicating that national languages still has the strongest position. Foreign language that is predominant in bilingual and multilingual signs is English. Gorter (2006) divides types of signs in linguistic landscape into two: bottom-up and top-down, type of sign that uses English the most is type bottom-up, displayed to live both informative function, which are to tell the name of shops and to do marketing and symbolic function, which are to symbolize modernity, sophistication, professionalism, and social status.